Therapeutic monitoring of amiodarone: pharmacokinetics and evaluation of the relationship between effect and dose/concentration - Hrudikova Vyskocilova, Erika; Grundmann, Milan; Duricova, Jana; Kacirova, Ivana (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2017)
Amiodarone is the most effective agent in the therapy of arrhythmias. However, the clinical effect of acute and chronic treatment is unclear and there are differences irrespective of comparable plasma/myocardial amiodarone and its metabolite desethylamiodarone concentations as well. Its unusual pharmacokinetics results in interindividual variation in plasma levels. The association between amiodarone and desethylamiodarone plasma levels and clinical efficacy is difficult to evaluate. This review was carried out to assess whether there is any objective correlation between amiodarone and desethylamiodarone plasma levels and the clinical effect. We summarized the results of relevant studies and clarified the relationship between plasma levels and effect vis á vis the pharmacokinetics and pharmacogenetics of this drug. Certain correlation was seen with oral amiodarone therapy, in others, plasma amiodarone levels were unrelated to therapeutic response and showed no correlation with changes in electrocardiogram or electrophysiological parametres. Several studies show that plasma concentration ranging between 0.5 and 2.5 mg/L appears to be the most effective, others demonstrate no difference between responders and non-responders. One way of interpreting plasma levels is to establish an individual patient´s effective concentration. Therapeutic drug monitoring can contribute to determining optimal concentration.
Keywords: amiodarone; Amiodarone; Male; amiodaron; effects; vztah mezi dávkou a účinkem léčiva; Adult; Aged; dospělí; mužské pohlaví; senioři; srdeční arytmie; Arrhythmias, Cardiac; senioři nad 80 let; lidé; ženské pohlaví; Humans; pharmacokinetics; Anti-Arrhythmia Agents; therapeutic drug monitoring; Aged, 80 and over; Female; Dose-Response Relationship, Drug; lidé středního věku; antiarytmika; Middle Aged